Shared decision-making in patients with multiple sclerosis - Ubbink, Dirk T.; Damman, Olga C.; de Jong, Brigit A. (Frontiers in Neurology, 2022)
Multiple sclerosis (MS) is a chronic and progressive neurological disorder impacting physical, cognitive, and psychosocial health. The disease course, severity, and presence of symptoms differ within and between persons over time and are unpredictable. Given the preference-sensitive nature of many key decisions to be made, and the increasing numbers of disease-modifying therapies, shared decision-making (SDM) with patients seems to be key in offering optimum care and outcomes for people suffering from MS. In this paper, we describe our perspective on how to achieve SDM in patients with MS, following key SDM-elements from established SDM-frameworks. As for deliberation in the clinical encounter, SDM communication training of professionals and feedback on their current performance are key aspects, as well as encouraging patients to participate. Concerning information for patients, it is important to provide balanced, evidence-based information about the benefits and the harms of different treatment options, including the option of surveillance only. At the same time, attention is needed for the optimal dosage of that information, given the symptoms of cognitive dysfunction and fatigue among MS-patients, and the uncertainties they have to cope with. Finally, for broader communication, a system is required that assures patient preferences are actually implemented by multidisciplinary MS-teams. As SDM is also being implemented in many countries within the context of value-based health care, we consider the systematic use of outcome information, such as patient-reported outcome measures (PROMs) and Patient Decision Aids, as an opportunity to achieve SDM.